Increased Organization Turnover : Job Satisfaction and Good HR Policies and Practices - Joshi, Anurag; Ratnesh, Kumar; Kothiwal, Ritu (Journal of Commerce and Trade, 2011)
Organizational turnover defined as the revenue generated by the organization in context of viable efforts made by its member whether they are managerial or technical persons, in terms of productivity. A positive drive or incline in productivity is an output of sum total of the practices like, Education, Scientific recruitment method, Critical Evaluation of Performance Appraisal, Revision of Compensation plans, Organizational development, flexible time hours, Effective communication system, Quality of Work life, Creativity & innovation, Knowledge Management and Reward & recognition system. These practices lead the satisfaction level of organizational member which provides tangible output in term of improved performance and hence organizational turnover with expanding the tenure and stability of both the organization and the one’s.